Mengembangkan Norma Sosiomatematik Dengan Team Accelerated Instruction - Sri Adi Widodo; Agustina Sri Purnami (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The sociomathematics’ norm is a social norm of mathematical nuance, with sociomathematics’ norms; the social intelligence possessed by learners can be developed because his norm is strongly associated with negotiation and interaction. The purpose of this article is to know the improvement of sociomathematics’ norms student of mathematics education by using cooperative learning of Team Accelerated Instruction. This research uses pretest-posttes control only group design. Sample size in this research is 38 people in class C of course of Numerical Method taken by cluster random. The sociomathematics’ norm is obtained using an observation sheet. The data obtained were analysed using N-gain and t-test (paired-samples T Test). Based on the result, it can be concluded that the learning model of Team Accelerated Instruction can improve students' sociomathematics’ norm ability through numerical method